Pediatric thoracic surgery - Lima, Mario (Springer Milan, 2013)
The past two decades have witnessed a technological revolution in surgery, leading to the widespread application of minimally invasive techniques. Such techniques have had a profound impact on the diagnosis and therapy of thoracic disorders, including in the pediatric age group. This book is intended as a practical guide to the current approaches in pediatric thoracic surgery. Up-to-date information is provided on the surgical techniques employed for diagnosis and therapy in a wide range of congenital and acquired thoracic pathologies from the prenatal age to adolescence. Among the disorders considered in detail are cystic malformations of the lung, chest wall deformities, diaphragmatic hernias, esophageal anomalies, mediastinal tumors, laryngeal anomalies, and thoracic infections. The authors are distinguished experts in the field from across the world. Pediatric Thoracic Surgery will be of value not only for pediatric thoracic surgeons but also for adult thoracic surgeons, pediatric anesthetists, and pediatric respiratory physicians.